- Thread starter Stine
- Start date

- Joined
- Apr 12, 2005

- Messages
- 9,784

2^2 = 4

(-2)^2 = 4

In your case:

1^2 = 1

(-1)^2 = 1

So, there are two results for 'x - 1/2'

x - 1/2 = 1 or x - 1/2 = -1

Solve each for 'x'.

(x - 1/2)^2 = 1

x^2 - x + 1/4 = 1

x^2 - x - 3/4 = 0

4x^2 - 4x - 3 = 0

(2x - 3)(2x + 1) = 0

x = 3/2 or x = -1/2

Oh oh: he's right; better call him "splendid" :wink:

- Joined
- Apr 12, 2005

- Messages
- 9,784

Normally, one would "Complete the Square" to solve such a thing. (Or use the general completed square known as the Quadratic Formula). In your problem, the square is already completed, so why undo it?